The perspective of environmental activists in responding to the Lapindo mudflow disaster in Sidoarjo Regency: A phenomenological study - Sabrina Kusuma Wardhani; Awan Setia Dharmawan (CV. Literasi Indonesia, 2026)
The Lapindo mudflow disaster that occurred on May 29, 2006, resulted in extensive social, economic, and ecological damage to communities in Sidoarjo Regency. Nearly two decades later, the recovery process continues to face persistent challenges, particularly concerning social injustice, loss of housing and livelihoods, and long-term environmental degradation. In response to these conditions, environmental movements emerged among affected communities as a form of collective resistance and advocacy. This study aims to identify and analyze the environmental movements formed by Lapindo mudflow victims and to examine how movement actors perceive and respond to the disaster. Employing a qualitative research design with a phenomenological approach, the study was conducted in Kedungsolo Village, which serves as a relocation area for displaced residents. Data were collected through in-depth interviews, field observations, and literature review to capture the subjective experiences and perspectives of environmental movement actors. The findings reveal that the environmental movement developed primarily as a response to perceived injustice, particularly regarding compensation disputes, delays in assistance, and inadequate living conditions in refugee camps. Collective action contributed to improvements in housing compensation; however, economic recovery remains limited and uneven. Additionally, the movement plays a significant role as a form of social action that mobilizes communities to assert their rights and demand accountability. The study highlights the importance of sustained government support and long-term economic empowerment initiatives to ensure comprehensive post-disaster recovery for affected communities.